Hubungan antara HER-2/neu dan Ki-67 dengan Respons Kemo-terapi Neoadjuvan pada Karsinoma Payudara Lanjut Lokal - I Made Jatiluhur; Anglita Yantisetiasti; Abdul Hadi Hassan; Bethy S Hernowo (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2015)
Background Locally advanced breast cancer (LABC) were stage III breast carcinoma based on TNM system, with an incidence >50% of all breast cancers in developing countries , including Indonesia. The first treatment of LABC is neoadjuvant chemotherapy, most often in anthracycline base. The purpose of this study is to analyze the relationship between HER-2/neu and Ki-67 with anthracycline-based neoadjuvant chemotherapy responsse in LABC. Methods The study involved 52 LABC, each of 26 patients responsding and not responsding. Paraffin block from biopsy stained with HER-2/neu and Ki-67 immunohistochemistry. HER-2/neu expression interpreted as positive and negative, while Ki-67 were categorized as